Online Geospatial Database and Processing of Universal Soil Loss Equation Modeling for Optimum Assessment of Soil Loss in Songkhram Sub-Watershed, Northeastern Thailand - Changnoi, Burin (Agriculture and Natural Resources, 2014)
An online geospatial database and processing system of universal soil loss equation modeling was designed and implemented, which included a distributed database designed to accommodate, organize and manipulate spatial data as well as interrelate data from various sources distributed by government offices. The system was used to produce erosion susceptibility maps for regions of Upper Northeastern Thailand—an area that has suffered from inappropriate land use practices. The OpenGeo software suite was used for online integration of the distributed database. GIS-based methods were proposed and applied to data from the Songkhram sub basin in the Mekong River basin. ArcGIS software was used to derive land use, land cover and topographical data for the watershed. An open source GIS (QGIS) and the Geographic Resources Analysis Support System (GRASS) package were used to carry out geographical data analysis and database management system implementation, both of which were implemented using the OpenGeo software suite. The watershed was mapped into topographically and geographically homogeneous grid cells to capture watershed heterogeneity. The results showed that during the study period, the area had soil losses that exceeded the tolerance level ranging from the moderate class up to the very severe class of susceptibility. Moreover, it was also found that the amount of soil erosion decreased to 499 km2 in 2010 from a predicted 1,123 km2.